2016
DOI: 10.1038/srep35901
|View full text |Cite
|
Sign up to set email alerts
|

von Willebrand factor contributes to poor outcome in a mouse model of intracerebral haemorrhage

Abstract: Spontaneous intracerebral haemorrhage (ICH) is the most devastating stroke subtype and has no proven treatment. von Willebrand factor (VWF) has recently been demonstrated to promote inflammation processes. The present study investigated the pathophysiological role of VWF after experimental ICH. Functional outcomes, brain edema, blood-brain barrier (BBB) permeability, cerebral inflammation and levels of intercellular adhesion molecule-1 (ICAM-1) and matrix metalloproteinase-9 (MMP-9) were measured in a mouse mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 50 publications
1
23
0
2
Order By: Relevance
“…To examine the effects of a combined rADAMTS13 and VWF approach on neovascularization and BBB permeability, human VWF (5 mg/mouse; Haematologic Technologies, Essex Junction, VT) was administrated IV with rADAMTS13 into mice once per day for 1 week. 25 Because the half-life of human VWF is very short in mice, 26,27 daily administration was performed. VEGFR-2 antagonist Su1498 (250 ng in 2 mL PBS containing 1% dimethyl sulfoxide; Abcam, Cambridge, MA), recombinant human galectin-3 (rGal-3; 5 mg/mouse; Peprotech, Rocky Hill, NJ) or rabbit anti-VWF antibody (6 mg/g body weight; Dako, Carpinteria, CA) was administered for 1 week.…”
Section: Treatment Regimensmentioning
confidence: 99%
“…To examine the effects of a combined rADAMTS13 and VWF approach on neovascularization and BBB permeability, human VWF (5 mg/mouse; Haematologic Technologies, Essex Junction, VT) was administrated IV with rADAMTS13 into mice once per day for 1 week. 25 Because the half-life of human VWF is very short in mice, 26,27 daily administration was performed. VEGFR-2 antagonist Su1498 (250 ng in 2 mL PBS containing 1% dimethyl sulfoxide; Abcam, Cambridge, MA), recombinant human galectin-3 (rGal-3; 5 mg/mouse; Peprotech, Rocky Hill, NJ) or rabbit anti-VWF antibody (6 mg/g body weight; Dako, Carpinteria, CA) was administered for 1 week.…”
Section: Treatment Regimensmentioning
confidence: 99%
“…Our preclinical studies have further confirmed that baseline CVR positively correlated with plasma levels of VEGF, VEGF-C, and P-selectin. Our results are consistent with other investigators' reports that elevated levels of IL-8 and sICAM-1 in the CSF may correlate with blood-brain barrier (BBB) dysfunction after TBI; sICAM-1 and TNF-α can induce macrophage inflammatory protein MIP-2 in astrocytes and microvascular endothelial cells; sICAM-1, selectins, and vWF were proposed as biomarkers of vascular endothelial damage and dysfunction [5,[11][12][13]; TBI upregulated VEGF, Flt-1, and Flk-1 [14].…”
Section: Discussionsupporting
confidence: 72%
“…In that regard, a common point in the studies described in the previous paragraph was that VWF deficiency or antibody‐mediated inhibition of VWF was associated with a significant decrease in vascular permeability (Fig. ) , whereas the addition of extra VWF resulted in increased vascular permeability in the experimental ICH‐model . Permeability has been differentially measured via the use of Evan's blue leakage, skin biopsy weight, or brain water content.…”
Section: Part 3: the Direct Role Of Vwf In Inflammationmentioning
confidence: 99%